The features of the influence of urban identity on the social and psychological adaptation of students - Olena Yevgenivna Blynova; Olena Borysivna Ursulenko (Insight: the psychological dimensions of society, 2020)
The purpose is to clarify the influence of the level of maturity of the urban identity on the social and psychological adaptation of students and satisfaction with life. Methods. The following methods were used in the empirical research: Urban Identity Questionnaire (S. O. Litvinova, O. I. Muravyova); Questionnaire of Social and Psychological Adaptation (C. Rogers & R. Diamond, adapted by O. K. Osnytsky); The Satisfaction with Life Scale of E. Diener adapted by D. O. Leontiev, Ye. M. Osin). Results. The article includes different theoretical viewpoints and scientific approaches to the substantiation of the concept “urban identity”. The structure of urban identity consists of cognitive, emotional and behavioral-regulatory components. The research shows the influence of mature identity on the social adaptation under urban conditions. The authors make the social and psychological analysis of differences between the urban and countryside lifestyles; they find out that urban lifestyle is based on a high spatial, professional and social mobility of urbanites. It is emphasized that urban identity has an axiological and logical nature as it sets norms and rules, which regulate human behavior while actualizing in different situations of social interaction. The empirical research clarified the features of the manifestation of students’ urban identity, its influence on the social and psychological adaptation of students, carries out a comparative analysis between a group of students who are original residents of the city and a group of students who moved into the city from the countryside to study at the university. Conclusions. The findings of the empirical research confirm the differences in terms of the social and psychological adaptation between the group of “urbanites”, i.e. students who were born and live in the city and the group of “country people” who moved into the city to study at the university. By using the correlation analysis, the authors prove the interdependence between the level of maturity of urban identity of students (cognitive, emotional and behavioral-regulatory components) and progress of social and psychological adaptation in the city. The research prospects are the development of means of psychological aid for the adaptation of students who come to the city to study at the higher education institutions.